PERSEPSI IBU PRIMIPARA TENTANG METODE KB IUD DI BPS Ny. FARIDA YULIANI DESA GAYAMAN MOJOANYAR MOJOKERTO - Dwiharini Puspitaningsih (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2019)
KB program has important contribution in order to improve the population quality. family planning goal is every pregnancy must be wanted, today many mothers have difficulty in determining the type of contraceptive choice. The low election of contraceptives are often influenced by factor parity, contraception maternal parity (primiparous) This study aims to determine perceptions of primiparous mothers about IUD family planning methods. This research type is variable in this study is the perception of primiparous mothers about family IUD planning methods. The population is all primiparous mothersas many as 35. The sample in this study is all primiparous mothers, sampling techniques that is used is the NonProbability Sampling. Data in this study is the primary data. The data stage processing through editing, coding, scoring, data entry, tabulating, data analysis Pshow in the form of a frequency distribution. From the results of the discussion above,it can be concluded that the majority of respondents perceived negative IUD birth as 14 respondents (63.6%) and the fraction of positive perceptions about the IUD birth by 8 respondents (3 6.4%) Suggested to midwife further increase the knowledge about the IUD birth order can be used as an additional reference in providing services to the community, while for respondents to be able to choose contraceptives that are safe for use in preventing the occurrence of next pregnancies.